New records of red seaweeds to the coast of Ceará State, northeastern Brazil - Soares,Luanda Pereira (2018)
ABSTRACT A recent floristic survey of Rhodophyta from Ceará State, Brazil (02º46'30''-07º52'15''S and 37º14'54''-41º24'45''W), revealed the occurrence of 113 species distributed into 14 orders, 28 families and 63 genera. Of these, 18 species belonging to seven orders are new records; some of them poorly described and illustrated in the literature or cited only checklists. Therefore, aiming to expand the taxonomic knowledge about these poorly known species, we present detailed descriptions, illustrations, and comments on related taxa. The occurrence of Ceratodictyon scoparium is confirmed for the South Atlantic coast. The male gametophytes of Dohrniella antillarum var. brasiliensis and tetrasporophytes of Gracilariopsis silvana are illustrated for the first time. Ceramium fujianum is a new addition to northeastern Brazil. Among the new records, Callithamnion corymbosum, Ceramium clarionense, C. fujianum and C. scoparium showed a significant expansion of their geographic distribution along the Brazilian coast. Most of the newly recorded species are filamentous, small-sized or tufted algae, highlighting the need for new collections to detect the presence of these components.